Gambaran Tingkat Pengetahuan Remaja Tentang Protokol Kesehatan Pada Masa New Normal Di SMK PGRI 3 Denpasar - Putu Noviana Sagitarini (JURNAL MEDIKA USADA, 2022)
Background: The application of health protocols to break the chain of spread of COVID-19, especially in adolescents, is very important. The application of health protocols to adolescents is influenced by various factors, one of which is the knowledge of adolescents about health protocols Purpose: This study aims to describe the level of knowledge of adolescents about health protocols during a pandemic at SMK PGRI 3 Denpasar. Methods: This type of research is descriptive with a cross sectional design. The number of samples as many as 191 students, sampling by means of probability sampling with simple random sampling, statistical tests using SPSS. The instrument in this study used a questionnaire distributed online via google form. Analysis of the data in a descriptive way to obtain a variable frequency distribution. Results: From the results of the study, it was found that 56% had good knowledge, 41.9% had sufficient knowledge, and 2.1% had poor knowledge. Conclusion: The level of adolescent knowledge about health protocols during the new normal period at SMK PGRI 3 Denpasar is good.